First report of the efficacy of a fluralaner-based pour-on product (Exzolt® 5%) against ectoparasites infesting cattle in Brazil - Alvimar José da Costa; João Ricardo de Souza Martins; Fernando de Almeida Borges; Luis Fernando Vettorato; Francisco Bonomi Barufi; Heitor de Oliveira Arriero Amaral; Luara Carolina Abujamra; Daniel de Castro Rodrigues; Welber Daniel Zanetti Lopes (Parasites & Vectors, 2023)
Abstract Background This study describes the effectiveness of a novel active pharmaceutical ingredient, fluralaner (isoxazoline class), against important ectoparasites infesting cattle in Brazil. Methods A total of 13 studies involving a 5% fluralaner-based pour-on formulation (Exzolt 5%; further referred to as Exzolt) were conducted. Specifically, the effectiveness of this formulation was studied against Rhipicephalus microplus (6 studies), Cochliomyia hominivorax larvae (4 studies), Dermatobia hominis larvae (1 study) and Haematobia irritans flies (2 studies). Results The therapeutic efficacy of Exzolt was found to exceed 98% at 4 days post treatment (DPT), while persistent efficacy (> 90% efficacy) against repeated infestations of R. microplus was observed for up to 79 DPT. In field studies, ≥ 98% therapeutic efficacy was demonstrated at all study sites by 7 DPT, and a persistent efficacy (> 90% efficacy) was observed for 42, 49 or 56 DPT. Exzolt prevented C. hominivorax eggs from developing to the larval stage, thus mitigating the development of myiasis in cattle naturally and artificially infested with this screworm. The efficacy of Exzolt against D. hominis larvae was 98% at 3 DPT, while persistent efficacy (> 90% effectiveness) was found to last for up to 70 DPT. Against H. irritans, Exzolt showed therapeutic efficacy (≥ 90%) within the first day of treatment at both study sites, while persistent efficacy (≥ 90%) was observed for 7 DPT at one site and for 21 DPT at the other site. Conclusions Overall, the results from these studies confirm that Exzolt is therapeutically efficacious against the most important ectoparasites infesting cattle in Brazil. The novel active pharmaceutical ingredient, fluralaner, provides a new treatment option for farmers to control cattle ectoparasites, especially where there is resistance to other chemical classes. In addition, an effective control of ectoparasites will improve overall cattle health and well-being as well as production. Graphical Abstract